2020
DOI: 10.3390/antiox9111083
|View full text |Cite
|
Sign up to set email alerts
|

Thymus vulgaris Essential Oil Protects Zebrafish against Cognitive Dysfunction by Regulating Cholinergic and Antioxidants Systems

Abstract: Thymus vulgaris L. is an aromatic herb used for medicinal purposes such as antimicrobial, spasmolytic, antioxidant, anti-inflammatory, antinociceptive, antitumor, and may have beneficial effects in the treatment of Alzheimer’s disease. The present study aimed to investigate whether Thymus vulgaris L. essential oil enhances cognitive function via the action on cholinergic neurons using scopolamine (Sco)-induced zebrafish (Danio rerio) model of memory impairments. Thymus vulgaris L. essential oil (TEO, 25, 150, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 78 publications
(86 reference statements)
5
43
0
Order By: Relevance
“…In a previous study, Zanandrea et al [ 46 ] showed that SCOP administration (100 µM for 1 h) to zebrafish did not alter the specific activity of AChE compared to control fish. In contrast, several other reports have demonstrated that SCOP (100 µM for 30 min) increased the activity of this enzyme in the zebrafish brains [ 36 , 37 , 38 , 92 , 93 ]. Ziani et al [ 41 ] showed that NIC (1 mg/L for 3 min) increases the AChE activity when it is co-administered with a compound that provokes a fear response in zebrafish but not when NIC is administered alone.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…In a previous study, Zanandrea et al [ 46 ] showed that SCOP administration (100 µM for 1 h) to zebrafish did not alter the specific activity of AChE compared to control fish. In contrast, several other reports have demonstrated that SCOP (100 µM for 30 min) increased the activity of this enzyme in the zebrafish brains [ 36 , 37 , 38 , 92 , 93 ]. Ziani et al [ 41 ] showed that NIC (1 mg/L for 3 min) increases the AChE activity when it is co-administered with a compound that provokes a fear response in zebrafish but not when NIC is administered alone.…”
Section: Resultsmentioning
confidence: 60%
“…The biochemical results obtained in this study indicated that COT and 6HLN exhibit an antioxidant profile in the SCOP-induced zebrafish model of AD. Several reports showed that SCOP treatment induces oxidative stress in the brain of zebrafish [ 36 , 37 , 38 , 92 , 93 ] or rodents [ 64 , 96 , 97 , 98 , 99 ]. In a cell line derived from Danio rerio gill tissue, NIC treatment (3–7 mg/L for 12 h) has been shown to induce intracellular ROS generation in a dose-dependent manner [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress is one of the pathways responsible for Sco-induced amnesia. The pro-oxidative effects of Sco have been documented as it decreases the activity of antioxidant enzymes such as SOD, CAT, and GPX [63,64] and increased the concentration of malondialdehyde (MDA), which is the main marker of lipids peroxidation [64,65]. Also, numerous studies have shown the pro-cognitive impact of antioxidant compounds on Sco-induced memory damage, possibly by attenuating oxidative stress markers [27,58].…”
Section: Effects Of Bay Leaf Incense (Bl) On the Hippocampus Oxidativmentioning
confidence: 99%
“…These emotional responses involve profound changes and specified activity patterns in the zebrafish brain [ 75 ]. Although a recent study has shown Thymol to improve the cholinergic nervous system and antioxidative stress in a cognitive dysfunction model [ 21 ], no supporting behavioural information could be found for zebrafish embryo. Yet, Thymol has been shown to affect the behaviour (depression- and antidepressant-like) of mice [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, horsetail ( Equisetum arvense ) was the first approved basic substance according to the European Regulation (EC) 1107/2009 [ 13 ], but, although not considered as a substance of concern, it has been associated with potential neurodevelopmental toxicity [ 14 ]. Likewise, “jurema preta” ( Mimosa tenuiflora ) has been described as teratogenic to higher vertebrates [ 15 , 16 ], and Thymol, the main monoterpene phenol isolated from plants from the Lamiaceae family such as Thymus vulgaris L. [ 17 ], has been shown to cause developmental abnormalities in chicken and zebrafish embryos [ 18 , 19 , 20 ] and to regulate cholinergic and antioxidant systems in cognitive dysfunctional zebrafish [ 21 ]. However, although current research shows its antifungal properties [ 17 , 22 , 23 ] and some commercial pesticide products based on natural compounds are available on the market, there is a lack of sufficient neurodevelopmental information, and further studies are needed to clarify their environmental risk to non-target organisms to define efficient and appropriate use patterns.…”
Section: Introductionmentioning
confidence: 99%